2020
DOI: 10.1002/jbmr.3975
|View full text |Cite
|
Sign up to set email alerts
|

β-Catenin Preserves the Stem State of Murine Bone Marrow Stromal Cells Through Activation of EZH2

Abstract: During bone marrow stromal cell (BMSC) differentiation, both Wnt signaling and the development of a rigid cytoskeleton promote commitment to the osteoblastic over adipogenic lineage. β‐catenin plays a critical role in the Wnt signaling pathway to facilitate downstream effects on gene expression. We show that β‐catenin was additive with cytoskeletal signals to prevent adipogenesis, and β‐catenin knockdown promoted adipogenesis even when the actin cytoskeleton was depolymerized. β‐catenin also prevented osteobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 94 publications
3
41
0
Order By: Relevance
“…Findings from several teams revealed that regulating the repressive mark H3K27me3 represents an important step during the differentiation of MSCs toward osteoblasts. It was demonstrated that the activity of the H3K27 demethylases Utx/Kdm6a and Jmjd3/Kdm6b is critical for erasing this mark from the promoter of the Runx2 and Sp7 genes ( Figure 1 ) and hence to induce their expression during osteogenesis ( Ye et al, 2012 ; Hemming et al, 2014 ; Rojas et al, 2015 ; Park-Min, 2016 ; Sepulveda et al, 2017b ; Cakouros and Gronthos, 2020 ; Sen et al, 2020 ). Additionally, an increased activity of the PRC2 complex that “writes” the H3K27me3 mark, can significantly limit the ability of MSCs to engage osteogenic differentiation ( Wei et al, 2010 ).…”
Section: Epigenetic Control Of the Expression Of Master Regulators Ofmentioning
confidence: 99%
“…Findings from several teams revealed that regulating the repressive mark H3K27me3 represents an important step during the differentiation of MSCs toward osteoblasts. It was demonstrated that the activity of the H3K27 demethylases Utx/Kdm6a and Jmjd3/Kdm6b is critical for erasing this mark from the promoter of the Runx2 and Sp7 genes ( Figure 1 ) and hence to induce their expression during osteogenesis ( Ye et al, 2012 ; Hemming et al, 2014 ; Rojas et al, 2015 ; Park-Min, 2016 ; Sepulveda et al, 2017b ; Cakouros and Gronthos, 2020 ; Sen et al, 2020 ). Additionally, an increased activity of the PRC2 complex that “writes” the H3K27me3 mark, can significantly limit the ability of MSCs to engage osteogenic differentiation ( Wei et al, 2010 ).…”
Section: Epigenetic Control Of the Expression Of Master Regulators Ofmentioning
confidence: 99%
“…Ezh2 activity has been implicated in cell fate determination and differentiation (36), as well as maintenance of the stem cell state in the mesenchymal linages (37).The complexity of these functions of Ezh2 was uncovered in studies of the skeletal tissues. Loss of Ezh2 in the osteogenic lineage resulted in reduced bone formation, but conditional loss of Ezh2 in uncommitted mesenchymal cells yields skeletal patterning defects, including shortened forelimbs, craniosynostosis and clinodactyly (17).…”
Section: Discussionmentioning
confidence: 99%
“…To understand what preserved proliferative ability means for MSC fate, we quantified the osteogenic and the adipogenic capacity of EP, EP + LIV, LP and LP + LIV groups. We have previously established the multipotentiality of MSCs at EP timepoints 23,27,[34][35][36][37][38][39] . In order to check the potential changes in basal mRNA expression at LP Figure 1.…”
Section: Improves Msc Differentiation Potential Into Osteogenic Amentioning
confidence: 99%